Developing And Standardizing A Psychometric Scale to Evaluate Professional And Teaching Performance of Physical Education Teachers at Open Education College In Light of Academic Accreditation Standards - Falah Kareem Jeleeb Muhammad, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The study aimed to develop and standardize a scale for evaluating  performance of male and female physical education teachers during lessons, to identifying level of performance of male and female physical education teachers during lesson by building a scale to evaluate this performance. Research problem was that current scale does not objectively evaluate performance of male and female teachers, as it relies on limited items within an annual teacher evaluation form whose items do not cover all aspects of performance evaluation during lesson.  The researcher used descriptive approach with a survey method to suit nature of problem, in addition to describing  research community and its sample and determining axes of scale, which included four axes, in light of opinions of experts and specialists. (59) items were identified and presented to a group of experts to show their validity. Exploratory experiment was carried out, main experiment construction experiment. Statistical analyses were also carried out for items of scale in terms of their discriminatory ability, internal consistency, and scientific basis of scale. Scale was standardized so that data could be statistically processed, standards derived, and levels determined. Results showed performance level of male and female physical education teachers at Open Educational College that it was an unacceptable level. Performance level of female physical education teachers during lesson is better than performance level of male teachers in all aspects of study.  most important recommendation was to use current scale in evaluating performance of physical education teachers.